Sexual Excitation/Sexual Inhibition Inventory (SESII-W/M): Adaptation and Validation Within a Portuguese Sample of Men and Women. Issue 6 (17th August 2016) - Neves, Cide Filipe; Milhausen, Robin R.; Carvalheira, Ana
Abstract : The SESII-W/M is a self-report measure assessing factors that inhibit and enhance sexual arousal in men and women. The goal of this study was to adapt and validate it in a sample of Portuguese men and women. A total of 1, 723 heterosexual men and women participated through a web survey, with ages ranging from 18 to 72 years old ( M   = 36.05,   SD =  11.93). The levels of internal consistency were considered satisfactory in the first four factors, but not in Setting and Dyadic Elements of the Sexual Interaction. Confirmatory factor analysis partially supported the six-factor, 30-item model, as factor loadings and squared multiple correlations pointed to problems with items mainly loading on those two factors. General fit indices were lower than the ones estimated by Milhausen, Graham, Sanders, Yarber, and Maitland (2010). Psychometric sensitivity and construct validity were adequate and gender differences were consistent with the original study. The six-factor, 30-item model was retained, but changes to the factors Setting and Dyadic Elements of the Sexual Interaction, and their corresponding items, were recommended in order to strengthen the measure.